TIPOLOGI RUMAH JAWA DI KAWASAN PERDESAAN SUMBER POLAMAN LAWANG - Fifi Damayanti; Agung Murti Nugroho; Herry Santosa (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
The house is a place of living things live. A basic requirement for this stay originated from human shaping social life, to live together and form a pattern settlement. The formation of the villages in the village SumberPolaman, Lawang usually starts from a group of people who form a small village then more and more perfect. This area is shaped and influenced by natural factors as well as the physical expression of the region and culture that has been passed down from generation to generation. The house located in the village of Lawang SumberPolaman generally in the form of a traditional rural home with a simple roof forms that are divided by type and function of each. The wall is in the form of a plank of wood, bamboo and brick wall. While generally still use plaster floor, but there are some homes that already use a ceramic material. The main purpose of writing to determine the typology of residential buildings form the population and settlement patterns that exist in the village SumberPolaman, Lawang. The method used is descriptive method qualitative approach to typology that is the way to describe and classify the various types of data related to residential buildings in the village SumberPolaman, Lawang.